TEHNIK DASAR PENULISAN KARYA ILMIAH PENDIDIKAN - Rumina, Rumina (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The research was carried out starting from the existence of a problem. Problems are